Brillouin Optical Microscopy for Corneal Biomechanics - Scarcelli, Giuliano; Pineda, Roberto; Yun, Seok Hyun (Investigative ophthalmology & visual science, 2012)
The mechanical properties of corneal tissue are linked to prevalent ocular diseases and therapeutic procedures. Brillouin microscopy is a novel optical technology that enables three-dimensional mechanical imaging. In this study, the feasibility of this noncontact technique was tested for in situ quantitative assessment of the biomechanical properties of the cornea. Brillouin light-scattering involves a spectral shift proportional to the longitudinal modulus of elasticity of the tissue. A 532-nm single-frequency laser and a custom-developed ultrahigh-resolution spectrometer were used to measure the Brillouin frequency. Confocal scanning was used to perform Brillouin elasticity imaging of the corneas of whole bovine eyes. The longitudinal modulus of the bovine corneas was compared before and after riboflavin corneal collagen photo-cross-linking. The Brillouin measurements were then compared with conventional stress-strain mechanical test results. High-resolution Brillouin images of the cornea were obtained, revealing a striking depth-dependent variation of the elastic modulus across the cornea. Along the central axis, the Brillouin frequency shift varied gradually from 8.2 GHz in the epithelium to 7.5 GHz near the endothelium. The coefficients of the down slope were measured to be approximately 1.09, 0.32, and 2.94 GHz/mm in the anterior, posterior, and innermost stroma, respectively. On riboflavin collagen cross-linking, marked changes in the axial Brillouin profiles (P < 0.001) were noted before and after cross-linking. Brillouin imaging can assess the biomechanical properties of cornea in situ with high spatial resolution. This novel technique has the potential for use in clinical diagnostics and treatment monitoring.